Nordic Penal Exceptionalism: A Comparative, Empirical Analysis - Crewe, Ben (The British journal of criminology, 2023)
Based on a survey administered in 13 prisons in England & Wales and Norway, as part of a research programme with explicitly comparative aims, this article seeks to address both the relative and absolute dimensions of the Nordic penal exceptionalism thesis. It outlines the consistently more positive results in Norway compared to England & Wales, explaining them primarily with reference to the former’s much higher quality and use of open prisons. At the same time, it emphasizes that, even in an unusually humane prison system, prisoners report considerable pain and frustration. The article also makes the case that comparative analysis should strive to be systematic, but that such comparisons are always imperfect, making methodological transparency all the more essential.